Weight loss for judo competition: Literature review and practical applications - Stavrinou, P. S.; Aphamis, G.; Giannaki, G. C.; Bogdanis, G. C. (The Arts and Sciences of Judo, 2022)
A large number of judo athletes engage in long-term and rapid weight loss practices. There is evidence to suggest that these practices may induce adverse effects on the physical and mental health of the judoka, but there are conflicting findings regarding the impairment of performance. Further investigation is required to examine whether the 16 h time-period between the weighing and competition is adequate to diminish any negative effects on health and performance. It has been suggested that in the case when the decrease in body weight is less than 5%, restoration of body fluids and muscle glycogen stores may diminish the negative consequences on performance. Considering the possible acute and long-term negative health consequences, rapid and/or excessive weight loss should be discouraged. Considering that athletes are influenced mainly by their coaches for weight loss, education of both coaches and athletes is needed to support the implementation of safe weight loss strategies for judokas.